Keragaman Penyakit pada Bibit Pre Nursery dan Main Nursery Kelapa Sawit di PT. Socfindo Kebun Bangun Bandar, Kec. Dolok Masihul, Kab. Serdang Berdagai Sumatera Utara - Suryansyah, Mhd. Rizky; Himawan, Achmad; Kristalisasi, Elizabeth Nanik (Program Studi Agroteknologi INSTIPER, 2024)
Oil palm productivity is influenced by the availability of quality seeds. One important factor includes making seeds or nurseries. Single stage and double stage are two categories included in the provision of seeds based on type. To evaluate the frequency and severity of disease attacks, this study aims to identify various diseases that attack oil palms in pre nursery and main nursery. From July to August 2024, research was conducted at the Bangun Bandar plantation, North Sumatra Province, in an oil palm nursery area managed by PT. Socfindo. Purposive sampling was used as a survey method. Abiotic diseases (stunted, curly, grass like leaves, curly, and not planted properly) and biotic diseases (leaf spots) are often found in prenurseries. On the other hand, abiotic diseases (stunt, wrinkled leaves, curled leaves, twisted leaves, incompletely opened leaves, twisted leaves and misplanting), biotic diseases (leaf spots) are also often found in the main nursery. In the pre-nursery, leaf spot was the largest percentage of disease attacks (25.50%), but in the main nursery it was 28.55%. At pre nursery, leaf spot disease (9.50%) and the main nursery (11.50%) had the highest level of disease attack severity, both of which were classified as light damage.